Treatment results of radiotherapy to both the prostate and metastatic sites in patients with bone metastatic prostate cancer. (5th April 2021) - Inaba, Koji; Tsuchida, Keisuke; Kashihara, Tairo; Umezawa, Rei; Takahashi, Kana; Okuma, Kae; Murakami, Naoya; Ito, Yoshinori; Igaki, Hiroshi; Sumi, Minako; Nakayama, Yuko; Shinoda, Yasuo; et al.
Abstract: Although systemic therapy is the standard treatment for metastatic prostate cancer, a randomized controlled trial showed radiotherapy to the prostate improved overall survival of metastatic prostate cancer patients with the low metastatic burden. Additionally, a randomized phase II trial showed that metastasis-directed therapy for oligo-recurrent prostate cancer improved androgen-deprivation therapy (ADT)-free survival. Therefore, administering radiotherapy to both prostate and metastatic regions might result in better outcomes. Thus, we report the treatment results of radiotherapy to both prostate and metastatic regions. Our institutional database was searched for patients who received radiotherapy to the prostate and metastatic regions. We summarized patient characteristics and treatment efficacy and performed statistical analysis to find possible prognostic factors. A total of 35 patients were included in this study. The median age was 66 years, and the median initial prostate-specific antigen (PSA) level was 32 ng/ml. The Gleason score was 7 in 10 patients, 8 in 13 patients, and 9 in 12 patients. The median radiotherapy dose was 72 Gy to the prostate and 50 Gy to the metastatic bone region. The 8-year overall survival, cause-specific survival, progression-free survival, and freedom from biochemical failure rate were 81, 85, 53, and 57%. Among the 35 patients, 12 were disease-free even after ADT was discontinued. In selected patients with metastatic prostate cancer, ADT and radiotherapy to the prostate and metastatic sites were effective. Patients with good response to ADT may benefit from radiotherapy to both prostate and metastatic regions.